What do we know about highly effective therapists? A systematic review - Pereira, Gladis Lee; Trujillo Sanchez, Carolina; Alonso-Vega, Jesús; Echevarría-Escalante, Daniel; Froxán-Parga, María Xesús (Anales de Psicología / Annals of Psychology, 2023)
Highly effective therapists are clinicians who systematically achieve excellent therapeutic outcomes. However, variables that could explain this performance still unknown. To identify these variables (i.e., definition, objective measurements; and the degree to which the independent variables measure what it claims) could help to know more about highly effective therapists’ performance. Therefore, a systematic review was conducted. Publications between 2000 and 2020 -from Scopus, MEDLINE/PubMed, Web of Science, PsycInfo, Google Scholar and ProQuest Research Library databases- were included. After analyzing 2784 empirical works, 31 studies have met the inclusion criteria. This systematic review allowed to identify, summarize, and define almost 50 variables that could predict therapists’ effects. The need to increase construct validity, to improve empirical designs, and to measure therapist-client interaction is discussed.